Deterministic light yield, fast scintillation, and microcolumn structures in lead halide perovskite nanocrystals - Maddalena, Francesco (2022)
Lead halide perovskite (LHP) nanocrystals (NCs) have recently attracted attention due to both their high quantum yield and their potential for X-ray imaging applications. In this paper, we investigated the scintillation properties of three different LHP NCs; CsPbBr3, FAPbBr3, and CsPbI3. The featured NCs exhibited high X-ray excited luminescence (XL) at cryogenic temperatures. While FAPbBr3and CsPbI3NCs display thermal quenching, CsPbBr3NCs show negative thermal quenching and high XL at high temperatures, with a light yield of 24,000 ± 2,100 photons/MeV at 300 K. The LHP NCs exhibit a small afterglow and low trap density and exhibit a very fast XL decay time, under 20 ns, faster than those of some currently used commercial scintillators. Overall, CsPbBr3NCs are the best performing materials investigated here, making them particularly attractive for fast-timing applications such as positron emission tomography or particle detectors in high-energy physics. In the end, we demonstrate the proof of concept for using a CsPbBr3NC matrix for imaging applications and the flexibility of NCs for developing microstructure scintillators.